FINGERPRINT SCANNERS - Bilinsky, Yosif; Yukish, Maryna; Pavliuk, Oleksandr (Scientific Works of Vinnytsia National Technical University, 2015)
The paper analyses the main methods of fingerprint scanning and presents the structures of main scanner types describing their advantages and disadvantages. There had been outlined the main problem of fingerprint scanning and ways for its solution.